THE EFFECTIVENESS OF CAKE APPLICATION ON STUDENTS’ SPEAKING SKILL IN ENGLISH CLASSROOM - Rahmadani AM, Andi Rizki; Latief, Hasnawati; Hafid, Hilda (English Language Teaching Methodology, 2024)
The purpose of this study was to determine the importance of using the Cake Application as a result of making speaking training materials. The Cake Application by itself indicates that the researcher created the content as a video using the Cake Application as the source. Research material is a dialogue in which questions are asked and responses are provided. Limitations Analysis of speaking ability in terms of pronunciation is the main emphasis of this study.Pretest and posttest are used in this research strategy, which is an experimental approach. Subjects In this study used sampling. An oral test was used to obtain data for this study. The Pretest and Posttest sections of the test are separated. Before speaking in front of the class, students are encouraged to engage in a debate about their opinion on Tiktok as part of the pretest. Students should engage in a debate about Instagram during the posttest, express their opinion, and then speak out loud in front of the classBased on the results of the pre-test and post-test, it was found that t count was 10,749 as the significant level with a degree of freedom 30 (df = 31 – 1 = 30, then obtained t table 1.679 from the average score of pre-test 65.48 and post-test 82.32. This shows that the Cake Application material has a significant effect on enhancing abilities speak students in proper pronunciation.